Implementasi Praktik Jual Beli Buah Mangga Dengan Sistem Borongan Ditinjau dari Perspektif Islam: Studi Kasus Desa Mbawa Kecamatan Donggo Kabupaten Bima - Hairul; Ihwan p. Syamsudin; Syarif Hidayatullah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In Mbawa Village, Donggo Subdistrict, there is a phenomenon of the practice of buying and selling mangoes carried out by the community. The researcher suspects that this practice is very detrimental to the mango fruit seller and is not contrary to Islamic law. The practice of buying and selling mangoes is based on observation and has been carried out for a long time by the community in Mbawa Village. So this research aims to find out the Implementation of the practice of Buying and Selling Mango Fruit with a Borongan System Viewed from an Islamic Perspective (Case Study of Mbawa Village, Donggo District, Bima Regency). This research will be conducted in Mbawa Village, Donggo District, Bima Regency, West Nusa Tenggara. This research uses Qualitative Research with a Case Study Approach. Data Collection Techniques are Observation, Interview and Documentation. Data Analysis Techniques are Data Reduction, Data Presentation and Conclusion Drawing. Based on the results of the study, it can be concluded that the practice of buying and selling mango fruit with a wholesale system in Mbawa Village is a local custom that has long been practiced by the community. This system makes it easy for farmers to sell their crops without having to be directly involved in the distribution or sales process one by one. Buyers also benefit from being able to obtain large quantities of mangoes directly from the plantation. Agreements are usually made through direct observation and verbal price negotiations, without detailed calculations of quantity and quality.